The Effect of Health Education with The Ladder Snake Game Media Against Children's Behavior in Choosing Snack in SD Negeri Bulusan Kecamatan Tembalang - Dieta Suryaningsih; Elsa Naviati (Universitas Muhammadiyah Semarang, 2019)
The behavior of having snacks while at school is a routine activity especially for elementary school students. Such behavior consists of knowledge, attitude, and action. One of the methods that can be applied in order to lessen the negative effects of consuming snacks is the health education using attractive media, such as snakes and ladders game. The purpose of this study is to comprehend the effects of health education using snakes and ladders game on student behavior in selecting snacks at Bulusan State Elementary School, Tembalang. This is a pre-experimental study with one group pretest-posttest without control group design. The population was all students from the 4th grade in Bulusan State Elementary School and consisted of 37 students who were selected using consecutive sampling method based on inclusion and exclusion criteria. The data was taken using questionnaire about knowledge, attitude, and action which were analyzed using Wilcoxon Signed Rank Test statistical analysis with the significant level of 0.05. The results shows that health education using snakes and ladder game affected the increase of knowledge with overall difference 5.308 (p=0.000), the increase of attitude with overall difference 4.813 (p=0.000), and the increase of action with overall difference 4.929 (p=0.000). It can be concluded that the health education using snakes and ladders game affects the student behavior in selecting snacks. It is suggested that the school officials use snakes and ladders as the media in giving information to the students.